Pattrens of NSM Syntax of Semantic Primitives Prototypes in the Fields of Custom and Religion in Bali - Netra, I Made (Udayana Journal of Social Sciences and Humanities; Vol 1 No 1 (2017): UJoSSH, Feburary 2017, 2017)
Efforts in documenting variations and clusterrs of Balinese lexicons, particularly in the fields of custom and religion, have been gradually made. The patterns of NSM syntax of prototypes of semantic primitives were thoroughly examined. Thus, an example of the use of the lexicon that represents each prototype of semantic primitives was made to complete the list of the lexicon previously studied.Therefore, NSM dictionary on prototypes of semantic primitives can be easily come into being.Data were obtained by the methods of participative observation, during which the techniques of Focus Group Discussion, recording, and note-taking were employed (Bungin, 2001:57; Moleong, 2000).In-depth interviews to several informants in the two regencies were carried out. The results of the interview were then cross-referenced to such key informants as tradition and community leaders. Data were comprehensively studied by the methods of padan of which relevant theories were used to study data and agih of which supporting equipment was sourced from the language itself (Sudaryanto, 2003). The results of data analysis showed that the patterns of NSM syntax were novelties by combination of several prototypes of semantic primitives accordingly. The patterns comprise of simple patterns, complex patterns, and the related specific patterns.